1910
DOI: 10.1002/jez.1400090105
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction and parasitism in the Unionidæ

Abstract: EXPLANATION OF FIGURES Gravid female of Ptychobranchus phaseolus. X 2Gravid female of Lampsilis subrostratus. Natural size.Gravid female of Obliquaria reflexa. Natural size.Gravid female of Quadrula ebena. X +.Gravid female of Lampsilis rectus. X 3.Gravid female of Symphynot,a complanata. X i.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
1

Year Published

1921
1921
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 1 publication
3
38
1
Order By: Relevance
“…Although earlier reports attributed encapsulation to either hyperplasia or cell movements (Lefevre & Curtis 1910, Young 1911, Arey 1932b, our results indicated that cell proliferation, transformation, and pseudopodial extension all contributed to capsule formation. Glochidia were initially surrounded by elongate cells, and later thickening and compaction of the capsule seemed to result from hyperplasia, cellular transformation, and cell migration.…”
Section: Discussioncontrasting
confidence: 96%
“…Although earlier reports attributed encapsulation to either hyperplasia or cell movements (Lefevre & Curtis 1910, Young 1911, Arey 1932b, our results indicated that cell proliferation, transformation, and pseudopodial extension all contributed to capsule formation. Glochidia were initially surrounded by elongate cells, and later thickening and compaction of the capsule seemed to result from hyperplasia, cellular transformation, and cell migration.…”
Section: Discussioncontrasting
confidence: 96%
“…Though the sister group relationship of Ambleminae and Gonideinae is not highly supported by ML in the F clade, it is consistent with the morphological taxonomy based on glochidial hook type [13,14,85,86] (Figure 3). …”
Section: Resultssupporting
confidence: 80%
“…Station personnel incorporated some of the first vocal advocates for mussel conservation, which included notable researchers such as Winterton C. Curtis, George Lefevre, Robert E. Coker, Thaddeus Surber, Arthur D. Howard and Max M. Ellis, producing a vast bibliography (e.g. Lefevre and Curtis, 1910;Coker et al, 1921;Howard, 1921). During the same period, Arnold Ortmann began a series of studies on the systematic analysis of anatomy, shell morphology and life history traits within the order Unionida (e.g.…”
Section: Important Events In Freshwater Bivalve Biology and Conservatmentioning
confidence: 99%